Association between admission haematocrit and mortality among men with acute ischaemic stroke. Issue 3 (24th April 2018) - Sico, Jason J; Myers, Laura J; Fenton, Brenda J; Concato, John; Williams, Linda S; Bravata, Dawn M
Abstract : Objective: Anaemia is associated with higher mortality among patients with non-stroke cardiovascular conditions; less is known regarding the relationship between anaemia and mortality among patients with acute ischaemic stroke. Methods: Medical records were abstracted for n=3965 veterans from 131 Veterans Health Administration facilities who were admitted with ischaemic stroke in fiscal year 2007. Haematocrit values within 24 hours of admission were classified as ≤27%, 28%–32%, 33%–37%, 38%–42%, 43%–47% or ≥48%. Multivariate logistic regression was used to examine the relationship between anaemia and in-hospital, 30-day, 6-month and 1-year mortality, adjusting for age, medical comorbidities, modified Acute Physiology and Chronic Health Evaluation-III and stroke severity. Impact factors were calculated to standardise comparisons between haematocrit tier and other covariates. Results: Among n=3750 patients included in the analysis, the haematocrit values were ≤27% in 2.1% (n=78), 28%–32% in 6.2% (n=234), 33%–37% in 17.9% (n=670), 38%–42% in 36.4% (n=1366), 43%–47% in 28.2% (n=1059) and ≥48% in 9.1% (n=343). Patients with haematocrit ≤27%, compared with patients in the 38%–42% range, were more likely to have died across all follow-up intervals, with statistically significant adjusted ORs (aORs) ranging from 2.5 to 3.5. Patients with polycythaemia (ie, haematocrit ≥48%) were at increased risk of in-hospital mortality (aOR=2.9; 95% CI 1.4 to 6.0), compared with patients with mid-range admission haematocrits. Pronounced differences between patients receiving and not receiving blood transfusion limited our ability to perform a propensity analysis. Impact factors in the 1-year mortality model were 0.46 (severe anaemia), 0.06 (cancer) and 0.018 (heart disease). Conclusions: Anaemia is independently associated with an increased risk of death throughout the first year post stroke; high haematocrit is associated with early poststroke mortality. Severe anaemia is associated with 1-year mortality to a greater degree than cancer or heart disease. These data cannot address the question of whether interventions targeting anaemia might improve patient outcomes.